Spatial And Socio-Demographic Patterns Of Urban Light Pollution And Future Interventions - Bódizs, Dalma; Zseni, Anikó (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Urban light pollution is an increasingly important environmental and public-health issue, yet its socio-demographic distribution within cities remains insufficiently explored. This paper presents an exploratory spatial comparison of nighttime illumination patterns and selected socio-demographic indicators in Győr, Hungary. The analysis draws on publicly available territorial statistics and mapped light-pollution data to examine whether areas with higher illumination intensity overlap with population groups that may be more vulnerable to nighttime environmental disturbance, particularly elderly and lower-income residents. Rather than testing causal relationships, the paper identifies indicative spatial patterns and evaluates the analytical potential of combining environmental and demographic datasets in urban research. The results suggest that the most intensely illuminated parts of the city are associated with the historical core, major transport corridors, and older high-density residential areas, which also show higher aging indices and less favourable income profiles. These findings point to a potential environmental inequality embedded in the city’s socio-spatial structure. From a policy perspective, the paper argues that lighting strategies should incorporate socio-demographic considerations alongside efficiency and safety objectives in order to support more equitable and sustainable urban governance.